Ultrahigh-performance liquid chromatography with tandem mass spectrometry for the determination of 10 alkaloids in beagle plasma after the oral administration of the three Coptidis rhizoma extracts. (15th July 2019) - Ren, Yixuan; Wang, Zhibin; Wu, Chengcui; Dong, Hongrui; Gan, Chunli; Fan, Linzi; Wang, Wenyu; Yang, Chunjuan
Abstract: Ethnopharmacological relevance: Coptidis rhizoma (CR ) is the dried rhizome of the ranunculaceous plant CR . For decades in China, this plant has been used to treat hypertension, hyperlipidemia, and chronic diarrhea and has been officially included in the Chinese Pharmacopoeia. The present paper presents a review of the pharmacokinetics of CR . Aim of the study: The pharmacokinetic studies and differences of 10 alkaloids among Coptis deltoidea C. Y. cheng et Hsiao, Coptis chinensis Franch and Coptis teeta Wall. Are seldom reported. This study is the first to determine corydaline, dehydrocorydaline, tetrahydropalmatine, palmatine, magnoflorine, jatrorrhizine, berberine, worenine, berberrubine, and coptisine, which adopted an ultrahigh-performance liquid chromatography-electrospray ionization-tandem mass spectrometry, simultaneously. Materials and methods: Chromatographic separation was performed within 8 min by using an Agilent SB-C18 column (150 mm × 2.1 mm, 1.8 μm) with gradient mobile phase consisting of 0.3% acetic acid water ( v / v) and acetonitrile at a flow rate of 0.3 mL/min. Multiple reaction monitoring mode was used to detect the tandem mass spectrum in the positive ionization mode by electrospray ionization source. Results: The method was fully validated to be linear over a wide concentration ( r > 0.9916), and the linear concentration range was 0.195–2260 ng/mL. Intra- and interday precisions were below 14.19% and 18.56% for the 10 analytes, respectively. The accuracy ranged from −9.30% to 6.31%. The extraction recovery of the 10 alkaloids and internal standard ranged from 79.76% to 95.37%. Pharmacokinetic comparative study showed that the C max and AUC0-∞ values of dehydrocorydaline, tetrahydropalmatine, palmatine, magnoflorine, jatrorrhizine, berberine, worenine, berberrubine, and coptisine increased significantly ( p < 0.05), which was different for beagles after oral administration. The results can help determine the mechanism of action and guide clinical application of these three extracts. Conclusion: This validated method was successfully applied for the pharmacokinetics study of beagle plasma after oral administration of three CR extract types. Graphical abstract: Image 1